STRATEGI PEMBELAJARAN BAHASA ARAB DI MADRASAH TSANAWIYAH HIFZHIL QUR’AN MEDAN - Beby Khairani; Dita Andini Harahap; Rahma Aswani (Yayasan Haiah Nusratul Islam, 2023)
Strategies and methods in learning Arabic are carried out so that students can learn and receive the material more effectively and efficiently. Teaching and learning strategies need to be designed and implemented when carrying out learning. Using good and appropriate learning strategies will produce maximum learning so that it can improve the quality of Arabic language learning. This research was conducted to look at the Arabic language learning strategies used at MTS Hifzhil Quran Medan. The research method used is a qualitative method, this method provides a focus point on the problem which is carried out by observation, interviews and other sample evidence. The results of the research show that the strategies used by teachers in learning Arabic at MTS Hifzhil Qur'an Medan are in learning Arabic vocabulary the teacher uses the strategy of playing games, in the Istima' Arabic learning strategy the teacher applies the strategy of listening to Arabic audio visuals, and in learning muhadastah Arabic teachers apply strategies for teaching the correct pronunciation of mukharijal letters.